A three-mask process for fabricating vacuum-sealed capacitive micromachined ultrasonic transducers using anodic bonding - Yamaner, F Yalçın (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2015)
This paper introduces a simplified fabrication method for vacuum-sealed capacitive micromachined ultrasonic transducer (CMUT) arrays using anodic bonding. Anodic bonding provides the established advantages of wafer-bondingbased CMUT fabrication processes, including process simplicity, control over plate thickness and properties, high fill factor, and ability to implement large vibrating cells. In addition to these, compared with fusion bonding, anodic bonding can be performed at lower processing temperatures, i.e., 350°C as opposed to 1100°C; surface roughness requirement for anodic bonding is more than 10 times more relaxed, i.e., 5-nm rootmean- square (RMS) roughness as opposed to 0.5 nm for fusion bonding; anodic bonding can be performed on smaller contact area and hence improves the fill factor for CMUTs. Although anodic bonding has been previously used for CMUT fabrication, a CMUT with a vacuum cavity could not have been achieved, mainly because gas is trapped inside the cavities during anodic bonding. In the approach we present in this paper, the vacuum cavity is achieved by opening a channel in the plate structure to evacuate the trapped gas and subsequently sealing this channel by conformal silicon nitride deposition in the vacuum environment. The plate structure of the fabricated CMUT consists of the single-crystal silicon device layer of a silicon-on-insulator wafer and a thin silicon nitride insulation layer. The presented fabrication approach employs only three photolithographic steps and combines the advantages of anodic bonding with the advantages of a patterned metal bottom electrode on an insulating substrate, specifically low parasitic series resistance and low parasitic shunt capacitance. In this paper, the developed fabrication scheme is described in detail, including process recipes. The fabricated transducers are characterized using electrical input impedance measurements in air and hydrophone measurements in immersion. A representative design is used to demonstrate immersion operation in conventional, collapse-snapback, and collapse modes. In collapsemode operation, an output pressure of 1.67 MPa pp is shown at 7 MHz on the surface of the transducer for 60-Vpp, 3-cycle sinusoidal excitation at 30-V dc bias